The Effect of He:Ne Laser on Viability and Growth Rate of Leishmania Major - . Al-Jeboory, Shaimaa R; Jassim, Awatif S.; Al-Ani, Rana R. (Iraqi Journal of Laser, 2007)
An isolate of Leishmania major was grown on the semisolid medium and incubated at 26ºC. The isolate was irradiated by He: Ne laser (632.8 nm, 10 mW) at exposure times (5, 10, 15, 20, 25, 30) minutes in their respective order. The unirradiated groups represent control group. Growth rate and percentage of viability were examined during six days after irradiation. The change in these two parameters reflects the effect of irradiation on the parasite. The results refers that the general growth effected by irradiation in comparison with un irradiation group, The growth rate of parasite decrease with increasing the exposure time in comparison with control group. Parasite viability decrease with irradiation and the percentage of living cell decrease with increasing of exposure time. High doses of laser at long exposure times increase the probability of damage this chromophore and leading to the negative effect on the parasite